Generation and characterisation of gallium titanate surfaces through hydrothermal ion-exchange processes - Wadge, Matthew D.; Stuart, Bryan W.; Thomas, Kathryn G.; Grant, David M. (Elsevier, 2018)
Infection negation and biofilm prevention are necessary developments needed for implant materials. Furthermore, an increase in publications regarding gallium (Ga) as an antimicrobial ion has resulted in bacterial-inhibitory surfaces incorporating gallium as opposed to silver (Ag). The authors present the production of novel gallium titanate surfaces through hydrothermal ion-exchange reactions. Commercially-pure Ti (S0: Cp-Ti) was initially suspended in NaOH solutions to obtain sodium titanate (S1: Na2TiO3) layers ca. 0.5–1 μm in depth (2.4 at.% Na). Subsequent suspension in Ga(NO3)3 (S2: Ga2(TiO3)3), and post-heat-treatment at 700 °C (S3: Ga2(TiO3)3-HT), generated gallium titanate layers (9.4 and 4.1 at.% Ga, respectively). For the first time, RHEED analysis of gallium titanate layers was conducted and demonstrated titanate formation. Degradation studies in DMEM showed S2: Ga2(TiO3)3 released more Ga compared to S3: Ga2(TiO3)3-HT (2.76 vs. 0.68 ppm) over 168 h. Furthermore, deposition of Ca/P in a Ca:P ratio of 1.71 and 1.34, on S2: Ga2(TiO3)3 and S3: Ga2(TiO3)3-HT, respectively, over 168 h was seen. However, the study failed to replicate the antimicrobial effect presented by Yamaguchi who utilised A. baumannii, compared to S. aureus used presently. The authors feel a full antimicrobial study is required to assess gallium titanate as a candidate antimicrobial surface.